Trade Unions in a Free Society - Dion, Gérard (Relations industrielles / Industrial Relations, 1956)
SummaryIn an industrial and democratic civilization, labor unionism appears as a normal and essential institution. Born of democracy, it helps to preserve and develop democratic life. There is, however, an essential condition. It must be itself an institution that really represents the workers and gives them the opportunity of expressing their aspirations while safeguarding their economic and professional interests. Union democracy is a necessity for the national welfare. But, above all, democracy in the labor movement is the direct responsability of union leaders who must ensure its maintenance and survival through good institutions and also by their cooperation in the civic education of the rank-and-file members.